Pola komunikasi dalam membangun budaya organisasi berdampak pada kinerja di TDW Grup - Hojanto, Ongky; Irwanti, Marlinda (Jurnal Mahardika Adiwidia, 2022)
The impact of Covid-19 Pandemic towards Tung Desem Waringin (TDW) Business Group of companies becomes an academic study on corporate culture yang communication carried out as a qualitative descriptive research. The study is prompted by the VUCA known as Volatility, Uncertainty, Complexity, and Ambiguity on Reshaping the Business Environment. Sunnie Gile who initiated the agile innovation approach by conducting all-hands meetingsÂ and speed up interactions on Reshaping the Business Environment has been applied. The recommendation of conducting a weekly meeting was followed through Zoom Webinar meetings which has resulted in positive staff members performance with the out-come that the positive aspects of TDW Groupâ€™s corporate culture becomes rooted, and as leaders are implementing well the necessary corporate communication. Further more, it did inspired the staff members in facing the difficult time as well as adjusting and coming-up with innovative ideas.